2014
DOI: 10.1016/j.vaccine.2014.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic hepatitis B virus infection before and after implementation of a hepatitis B vaccination program among children in Nepal

Abstract: Background In Nepal, an estimated 2–4% of the population has chronic hepatitis B virus (HBV) infection. To combat this problem, from 2002–2004, a national three dose hepatitis B vaccination program was implemented to decrease infection rates among children. The program does not currently include a birth dose to prevent perinatal HBV transmission. In 2012, to assess the impact of the program, we conducted a serosurvey among children born before and after vaccine introduction. Methods In 2012, a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…The reference standards used were CMIA in 5 studies, MEIA in 3 studies, and EIA/ELISA in 25 studies, with 3 studies using more than one type of reference assay. Test evaluations were conducted in 23 countries: six studies were conducted in high-income country studies [ 23 , 27 , 29 , 32 , 38 , 42 ], two in upper-middle income country studies [ 14 , 34 ], nine in lower-middle income [ 21 , 24 , 28 , 30 , 31 , 33 , 35 , 39 , 47 ], and six in low income [ 18 , 20 , 22 , 40 , 43 , 46 ] countries, with income levels classified according to the World Bank ranking criteria. The overall pooled sensitivity and specificity were 90.0% (95% CI: 89.1, 90.8) and 99.5% (95% CI: 99.4, 99.5), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference standards used were CMIA in 5 studies, MEIA in 3 studies, and EIA/ELISA in 25 studies, with 3 studies using more than one type of reference assay. Test evaluations were conducted in 23 countries: six studies were conducted in high-income country studies [ 23 , 27 , 29 , 32 , 38 , 42 ], two in upper-middle income country studies [ 14 , 34 ], nine in lower-middle income [ 21 , 24 , 28 , 30 , 31 , 33 , 35 , 39 , 47 ], and six in low income [ 18 , 20 , 22 , 40 , 43 , 46 ] countries, with income levels classified according to the World Bank ranking criteria. The overall pooled sensitivity and specificity were 90.0% (95% CI: 89.1, 90.8) and 99.5% (95% CI: 99.4, 99.5), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Strengths of this review include evaluation of a comprehensive evidence base, use of a pre-specified protocol incorporating numerous major scientific databases, and assessment of additional areas relevant to HBsAg diagnostic testing, notably comparison with NAT and potential impact of occult hepatitis B. We identified 11 additional articles [ 18 , 22 , 25 , 28 , 29 , 35 , 37 , 43 , 45 47 ] not found in the most recent systematic review assessing the diagnostic accuracy of RDTs [ 11 ]. The pooled sensitivity for RDTs in this review is lower than reported in previous systematic reviews (pooled sensitivities of 97.1% [ 11 ], 94.8% [ 10 ], and 98.1% [ 9 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The protective efficacy of vaccine is well established [ 9 12 ]. Recent studies conducted in different parts of the world have shown that there is a substantial reduction in Hepatitis B infections following introduction of vaccination program [ 13 15 ]. The most surprising finding of the study was that only 44.4% of the students were vaccinated with Hepatitis B vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In the US and other western countries, alcohol-related cirrhosis, and possibly nonalcoholic fatty liver disease associated with obesity, is account for the majority of liver cancer cases. Chronic infections with hepatitis B virus (HBV) and hepatitis C virus (HCV) are associated with less than half of liver cancer cases in the US, although they are the major risk factors for the disease worldwide (Upreti et al, 2014). Although chemotherapy is the mainstay of cancer therapy, the use of available chemotherapeutics is often limited mainly due to undesirable side effects and a limited choice of available anticancer drugs (Goutham Vemana et al 2014).…”
Section: Introductionmentioning
confidence: 99%